Short-term mortality following COVID-19 vaccination in Bologna, Italy: a one-year study. Issue 39 (16th September 2022) - Stivanello, Elisa; Beghelli, Chiara; Cardoni, Francesco; Giansante, Chiara; Marzaroli, Paolo; Musti, Muriel Assunta; Perlangeli, Vincenza; Todeschini, Renato; Pandolfi, Paolo
Abstract: The main objective of the study is to assess whether there is an increased risk of mortality in the days following the administration of COVID-19 vaccines in Bologna Health Authority in the first year of COVID-19 vaccination campaign. A secondary objective was to describe causes of deaths occurred in the days after vaccination. We conducted a retrospective observational study on all residents of Bologna Health Authority who received at least one COVID-19 vaccination dose from December 27, 2020 to December 31, 2021 and compared mortality in the 3, 7, 14 30 days after vaccination (risk interval) with the mortality in the period of the same length (3, 7, 14 and 30 days) beyond the 30th day after the last dose of vaccination (control interval). The cohort included 717, 538 people. The mortality rate was 2.24 per 100 person-years during the 30 days risk interval vs 2.72 in the control interval with an adjusted incidence rate ratio equal to 0.76 (95% CI: 0.70–0.83, p < 0.001). The risk of mortality is significantly lower (p < 0.001) also in the 3, 7, 14 days risk intervals than in the control intervals. This study shows that there is no increase in mortality in the short-term period after COVID-19 vaccines.